Alat Redestilasi sebagai Solusi Peningkatan Kualitas Asap Cair di Dusun Semen, Magelang - Nur Hidayah; Sabda Alam; Aldi Riyanto; Dwi Rahmasari Fatmawati; Dewi Rizqiyana; Mokhammad Fajar Pradipta; Fandika Agustiyar (STAI Auliaurrasyidin Tembilahan, 2022)
Women's Farmers Group (KWT) Nira Lestari became one of the groups engaged in the use of coconuts. Products produced by KWT Nira Lestari include liquid sugar, ant sugar, VCO and liquid smoke. The processing of products on KWT is not fully optimal, the liquid smoke produced cannot be used as a food aroma such as the function of liquid smoke in general because the processed results of liquid smoke are still pitch black and contain carcinogen compounds. This activity aims to design a liquid smoke redefiment technology at KWT partner Nira Lestari. The methods used include a specific review of the needs and potential of partners, preparation of implementation, technology design, analysis of tool concept design, video creation of program implementation, creation of product application playbook, and evalusai with partners. The results achieved from this activity are in the form of a design of liquid smoke distillation technology, video and application usage manual. The design of this distillation technology design is expected to be applied independently by partners, thus becoming a tool that has the potential to improve the quality of liquid smoke products and increase partner productivity.